Influence of Self-Efficacy as a Mediator on Time Management and Students’ Performance Relationship in Malaysian Online Distance Learning Institutions - Zahir Osman; Wardah Mohamad; Ratna Khuzaimah Mohamad; Liana Mohamad; Tuan Fatma Tuan Sulaiman (RMP Publications, 2018)
The main purpose of this study is to develop a mediating effect understanding of self-efficacy on time management and students’ performance relationship in Malaysian online distance learning institutions. A model was developed and later tested by adopting the partial Least Square (PLS) procedure on data collected from a survey that yielded 210 usable questionnaires. The findings showed that time management enhanced self-efficacy in Malaysian online distance learning institutions. It was also revealed that self-efficacy partially mediates the relationship between time management and students’ performance. In future, more research needs to be carried out to explore the role of self-efficacy in Malaysian online distance learning institutions. It is important to do the study utilizing experimental design by capturing longitudinal data in Malaysian online distance learning institutions using robust measures. The findings imply that the relationship between self-efficacy and attrition rate may reside in self-efficacy’s influence on students’ performance, and that self-efficacy plays a crucial function within the Malaysian online distance learning institutions. This study uses Smartpls 2.0 and SPSS 18.0 to test the hypothesis and analyze respondents’ profile respectively. (Abstract by authors)